Identification of Bipolaris sorokiniana-responsive differential transcripts in wheat (Triticum aestivum L.) - AGGARWAL, RASHMI; KHAREBIKAR, LALIT L.; RENU, AND (Indian Phytopathology, 2011)
Differential display reverse transcriptase polymerase chain reaction (DDRT-PCR) is used to identify transcripts induced by Bipolaris sorokiniana infection in wheat (Triticum aestivum L.). Using this method, we have identified two mRNA transcripts that are up- or down-regulated following B. sorokiniana infection. With 12 primer combinations, a total of 93 differential display products were observed in resistant genotype, BH1146 compared to 89 differentially displayed products in susceptible genotype, Sonalika. These products demonstrated qualitative and quantitative differences in the expression. The differentially expressed transcripts were collectively named WTRB (Wheat Transcripts Responsive to Bipolaris). We have identified two WTRBs, which were significantly altered due to B. sorokiniana infection. Both WTRB-1 and WTRB-2 expressed for longer period in resistant line compared to the susceptible line and may be used as molecular markers for screening wheat lines for spot blotch resistance.